2023
DOI: 10.1152/jn.00043.2023
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of persistent inward currents in lower limb motoneurons are larger in females than in males

Abstract: Non-invasive recordings of motor unit (MU) spike trains help us understand how the nervous system controls movement and how it adapts to various physiological conditions. The majority of participants in human and non-human animal physiology studies are male, and it is assumed mechanisms uncovered in these studies are shared between males and females. However, sex differences in neurological impairment and physical performance warrant the study of sex as a biological variable in human physiology and performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 83 publications
1
12
2
Order By: Relevance
“…Moreover, it remains unclear whether there are sex differences in PICs. The absence of differences in GM ΔF between males and females reported in our current and previous studies (Mesquita et al, 2022) contrasts with recent evidence of greater ΔF in lower limb muscles of females (Jenz et al, 2023). However, current observations are based on small sample sizes (up to 9 vs. 9 in our observations and 10 vs. 10 in Jenz et al, 2023) and future studies could usefully include a greater number of females and males.…”
Section: Lack Of Change In δFcontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, it remains unclear whether there are sex differences in PICs. The absence of differences in GM ΔF between males and females reported in our current and previous studies (Mesquita et al, 2022) contrasts with recent evidence of greater ΔF in lower limb muscles of females (Jenz et al, 2023). However, current observations are based on small sample sizes (up to 9 vs. 9 in our observations and 10 vs. 10 in Jenz et al, 2023) and future studies could usefully include a greater number of females and males.…”
Section: Lack Of Change In δFcontrasting
confidence: 99%
“…The absence of differences in GM ΔF between males and females reported in our current and previous studies (Mesquita et al, 2022) contrasts with recent evidence of greater ΔF in lower limb muscles of females (Jenz et al, 2023). However, current observations are based on small sample sizes (up to 9 vs. 9 in our observations and 10 vs. 10 in Jenz et al, 2023) and future studies could usefully include a greater number of females and males. Another important factor to consider in the future is the possible effect of sex hormone variation during the menstrual cycle on synaptic inhibition (Haage et al, 2002), neuromodulation (Bethea et al, 2002;Koldzic-Zivanovic et al, 2004;Smith et al, 2004) and, thus, PIC activity.…”
Section: Lack Of Change In δFcontrasting
confidence: 99%
“…When comparing across the cycle, MUP area was greatest in the mid luteal phase at both contraction levels. We have previously reported that at a given contraction level, females have smaller MUPs than males but possibly compensate for this with higher comparative firing rates [ 51 ], likely mediated by larger PIC estimates [ 73 ]. The same may be true here, where MUP area is greater when firing rate is lowest, indicating a minor alteration of recruitment strategy during the mid-luteal phase, compensating for reductions in firing rate at the same relative contraction intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, evoked responses from motor cortical and cervicomedullary stimulation are possibly less affected than the volitional activity of spinal motoneurones by dendritic PICs. Another consideration for this study is that fluctuations in estradiol and progesterone associated with the menstrual cycle could influence serotonergic modulation of motor activity (Bethea et al, 1998; Jenz et al, 2023; Sherman & Korenman, 1975). However, as only two females were included in our analysis we contend that the effects of sex had minimal effects on the results.…”
Section: Discussionmentioning
confidence: 99%